Gymnastics in Pedro II’s Collegio: a practice shared by its masters (Educação e Pesquisa, 2023)
This study has as thread the circulation, through Rio de Janeiro in the second half of the 19th century, of three gymnastics masters: Paulo Vidal, Vicente Casali and Arthur Higgins. By bringing them to the centre of this story, our goal is to understand, from their trajectories, which gymnastics was forged by them, at the same time, shared at the Collegio’s Pedro II during the 1800s. We hypothesize that the transit and performance in several different institutions contributed significantly to the systematization of gymnastics in that school. In order to do so, besides analyzing the teaching programs developed by them, we will cross-reference with other sources and data obtained in the newspapers of the time, which allow us to identify not only the institutions through which they circulated but also the constitutive elements of this corporal practice. In conclusion, we highlight that, in the process of systematizing gymnastics in Pedro II’s Collegio, there were negotiations among its masters to legitimize gymnastics, using different elements obtained in the school and non-school institutions through which they circulated. Thus, when we verify that the practice of gymnastics was part of the formative path of Pedro II’s Collegio, we cannot affirm that it was a single gymnastics. Therefore, the gymnastics forged and shared by the three teachers were embodied in their experiences and trajectories; for that reason, they had a transformative dimension that was adequate to the time and space in which they were shaped.